A profile of the design features of selected brands of basic jeans - Dela Rosa, Jessica Maica (College of Home Economics, University of the Philippines Diliman, 2009)
The general objective of the study was to establish o profile of the selected basic jeans available in the local market. Specifically, it aimed to determine the current fit, cut, silhouette and details of the basic jeans and and to identify the common style features of basic jeans among selected brands. This study can be used as a reference for marketers, manufacturers and innovators of basic jeans as it provides a snapshot of the basic jeans' characteristics at present time. This is a descriptive research study using the survey method. The researcher used purposive sampling wherein selected brands of basic jeans available were chosen based on their price ranges. The researcher utilized ocular survey and documented the design features of basic jeans from different brands in SM North EDSA department store with the use of specification sheets. Using descriptive statistics such as frequency distribution and percentage, data gathered were presented through tables. Qualitative approach of data analysis from the ocular survey and observations was used. The researcher analyzed the data that were [presented in a structured quantitative form. Four categories for basic jeans were indicated in this profile. The categories were fit, cut, silhouette and details which includes pockets, belt loops, rivets, bar tacks, and embellishments. Results showed that different combinations of these categories were present in the selected brands observed regardless of their price range. The data revealed that there were types under each category that were dominantly observed as compared to other types. Features included tight fit, pegged or skinny silhouette and low-waist cut were observed as the prevailing types. It is observed that currently, the styling for basic jeans is body hugging or those that provide emphasis on the curves or contours of the body. The detail category which includes pocket styling, belt loops, rivets, and bar tacks were observed to be utilized in regular or classic ways and functions with some modifications on materials, placement, shape or numbers. Significantly, embroidery, a form of embellishment, was greatly employed on selected basic jeans and was commonly used for indicating brand logos. From the results gathered and analyzed, the researcher concluded that the current sty;es of basic jeans available in the local market have not undergone radical changes from its classic form. Combination of different design features were employed to differentiate one style from another. Modification on parts or introduction of different materials was also utilized as part of basic jeans' innovations and changes to follow the current trends in the local market.